Nanoporous aerogel-based periodic high-energy electron current x-ray sensors - Brivio, Davide; Albert, Steffen; Gagne, Matt P.; Freund, Erica; Sajo, Erno; Zygmanski, Piotr (Journal of physics. D, Applied physics, 2020)
We developed a novel platform of self-powered radiation sensors based on high-energy electron currents in multi-layer thin-film geometry. A periodic structure of N elemental modules consisting of (high-Z electrode/nano-porous aerogel/low-Z electrode) layers was investigated. 10 and 50 μm thick high-Z (Cu, Ta) and low-Z (Al) electrodes were separated by 50 μm thick polyimide aerogel insulating films. Sensors were tested with 120 kV, 2.5 MV and 6 MV x-rays. The sensors’ characteristics were investigated by obtaining current-voltage (IV) curves for different low-Z/high-Z electrode combinations. Experimentally measured currents from each electrode were compared to radiation transport simulations using the CEPXS/ONEDANT computer model with nanometer-to-micrometer spatial resolution. The main features of the IV-curves are: (a) non-zero current at zero external voltage bias (b) S-like shape at small voltages, and (c) a linear increase of current dominant at large voltages. Signals scale with the total effective area of all electrodes, as well as the number of electrodes and their thicknesses. The yield of a multi-element sensor made with N = 10 elemental modules (10 μm-thick Ta) compared to a single N = 1 (double N = 2) elemental module (made with 50 μm-thick Ta layers) reveals an increase of the total signal of about 4.3 (2.9) times for 6 MV beam and 8.2 (5.8) times for 120kVp. Beam attenuation in the detector is about 0.5%, 3% and 46% respectively for 6 MV, 2,5 MV and 120kVp beams per single elemental structure with 50 μm Ta. We investigated the characteristics of aerogel-based high-energy current x-ray detectors in multi-layered configurations. We envision its implementation for real-time monitoring of radiation dose/flux in areas of homeland security, interventional radiology and radiotherapy.
Gesehen am 10.06.2020